Dialogic literary gatherings in out-of-home care to overcome educational inequalities by improving school academic performance. (February 2022) - Salceda, Marifa; Vidu, Ana; Aubert, Adriana; Padros, Maria
Highlights: Specific actions reverse adverse impacts produced by living in deprived contexts. Dialogic Literary Gatherings increase the academic achievement of out-of-home girls. Good school attainment prepare pupils in residential care for independent living. Egalitarian dialogue encourages children to promote changes in their environment. Social workers may increase their academic expectations towards all children. Abstract: There is much research revealing the educational inequality that affects children and youth in out-of-home care. Some reasons are the institutionalization impact on cognitive, social, and language development; problems of coexistence, or the low expectations of caregivers about their academic possibilities, leading to high rates of school failure and early school leaving. However, there is a lack of knowledge about which specific actions could reverse these adverse impacts and contribute to overcoming educational inequality in disadvantaged contexts. This paper analyzes a Dialogic Literary Gatherings intervention with 13 adolescents and 7 social workers on a group home for the protection and preparation for independent living of victims of family violence and neglect. Monthly Dialogic Literary Gatherings were developed with teenagers between 15 and 18 years old. Data collection consisted of a focus group of 5 adolescents, 2 in-depth interviews with adolescents and 2 in-depth interviews addressed to social workers. School results before and after the intervention have also been analyzed. The research was developed through the Communicative Methodology, which made it possible to analyze the components of the Dialogic Literary Gatherings that contribute to increase academic achievement in this environment. This approach involves the participants through an egalitarian dialogue that encourages them to promote changes in their environment. Beyond simultaneous improvements in the social and emotional well-being of the participants, our findings suggest improvements in the increase of their academic expectations, which reverse in positive progress of their school academic achievements after the intervention.